Recent Publications (Quarterly Journal of Economics, 1963)
Recent Publications Get access The Quarterly Journal of Economics, Volume 77, Issue 1, February 1963, Pages 180–184, https://doi.org/10.1093/qje/77.1.180 Published: 01 February 1963